Ethanol exposure interacts with training conditions to influence behavioral adaptation to a negative instrumental contingency - Mangieri, Regina A.; Cofresí, Roberto U.; Gonzales, Rueben A. (Frontiers in Behavioral Neuroscience, 2014)
We previously reported that, in male, Long Evans rats, instrumental lever pressing that had been reinforced during limited training under a variable interval (VI) schedule by oral self-administration of a 10% sucrose/10% ethanol (10S10E) solution was insensitive to devaluation of 10S10E. In contrast, lever pressing that had been reinforced under a variable ratio (VR) schedule, or by self-administration of 10% sucrose (10S) alone, was sensitive to outcome devaluation. The relative insensitivity to outcome devaluation indicated that seeking of 10S10E by the VI-trained rats had become an instrumental habit. In the present study we employed an alternative operational definition of an instrumental habit and compared the effect of reversing the action-outcome contingency on lever press performance by rats trained under the same experimental conditions. Male Long Evans rats received daily operant training, in which lever presses were reinforced by 10S10E or 10S, under VI or VR schedules. After nine sessions of VI or VR training, rats were tested over four sessions in which the instrumental contingency was changed so that a lever press would prevent reinforcer delivery for 120 s. We found that rats that had been trained to lever press for 10S10E under the VR schedule showed a greater change in lever pressing across testing sessions than those that had received 10S10E reinforcement under the VI schedule. There was no such interaction with reinforcement schedule for rats that had received only 10S reinforcement during training. These findings are consistent with those of our previous study, and provide further evidence that addition of ethanol to sucrose may promote habitual responding in an instrumental task.